PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN - Nisa, Walda Isna (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Abstrak:This study aims to determine the influence of leadership style and work motivation on the lecturers performance. This study uses a quantitative approach with survey research. Samples used a population sample that is taken from all of lectures (Fixed or not fixed) Faculty of Sains and Technology, Unira Malang as many as 24 people. Data analysis uses the prerequisite test and multiple linear regression analysis to determine the influence of leadership style and motivation of lecturers working on the lectures performance either partially or simultaneously. Based on the research we concluded that leadership style positive and significant effect on the lecturers performance. Work motivation no significant effect on the lecturers performance. Based on the f-test (simultaneously) note that the leadership style and work motivation have a significant effect on the lecturers performance. Simultaneously leadership style and work motivation influence on the lecturers performance 83.5%, while 16.5% were influenced by variables or other factors not examined.